Why Do Students Keep Using TikTok, Examining the Roles of Informative Value, Entertainment, and Satisfaction - Raihan Kamilun Amin; Adnan Kasofi; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2026)
This study aims to analyze the effects of informative value and entertainment on user satisfaction and their influence on continuous intention to use TikTok among university students. A quantitative approach was employed using a survey method. Data were collected from 97 students of Universitas Negeri Jakarta who had been using TikTok for more than one year. The data were analyzed using statistical techniques in SPSS, including validity testing, reliability testing, and structural model analysis.The results show that informative value and entertainment have positive and significant effects on user satisfaction. Entertainment demonstrates a stronger influence, indicating that enjoyable and engaging content plays a major role in shaping positive user experiences. In addition, user satisfaction has a strong and significant effect on continuous intention to use TikTok, suggesting that satisfied users are more likely to continue using the platform over time.The study concludes that both informational and entertainment aspects are essential in enhancing user satisfaction and encouraging sustained usage behavior. These findings imply that digital platforms and content creators should balance informative and entertaining content to maintain user engagement and long-term platform sustainability.